Breathing space : cross-community professional theatre as a means of dissolving fixed geographical landscapes - Matchett, Sara (Department of Drama, 2014)
In this paper, I investigate the idea of cross-community professional theatre as a means of dissolving fixed georgraphical landscapes. Key to this is the synergy between mainstream and community theatre, out of which this idea emerges. I explore how theatre facilitates conversations across differences. 'Differences' encompass questions of geographical, class and racial divides as well as the ideological differences between mainstream and community theatre. Cross-community professional theatre involves working with people from different communities around specific issues. Professional actors work alongside non-professional actors from communities to create a piece of theatre. Community members are involved in the process as well as in the performance. Cross-community refers not only to the exchange between professional actors and non-professional actors, but also to the idea of theatre providing a framework for conversations between different communities.